Language Translation in Localizing Religious Musical Practice - MacInnis, John; Perigo, Jeremy (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
The focus of this Special Issue is language translation in the process of localizing religious musical practice. As an alternative to related concepts (such as contextualization and indigenization), musical localization is presented by ethnomusicologists Monique Ingalls, Muriel Swijghuisen Reigersberg, and Zoe Sherinian in Making Congregational Music Local in Christian Communities Worldwide (Routledge, 2018) as an effective way to account for the complex, diverse, and shifting ways in which religious communities embody what it means to be local through their musical practices: "Musical localization is the process by which Christian communities take a variety of musical practices - some considered 'indigenous,' some 'foreign,' some shared across spatial and cultural divides; some linked to past practice, some innovative - and make them locally meaningful and useful in the construction of Christian beliefs, theology, practice, and identity." (13) This Special Issue shows the balance of translation priorities that local congregations can weigh as they work, between externally prescribed guidelines and exclusively local realities; between translations more oriented to the source language and culture, making that reality more plain, or to the recipients, ensuring that the meaning is adequately transferred to a new context; and between even the decision to translate or not, perhaps choosing to sing the songs of another culture and language as they are while risking appropriation.